2022
DOI: 10.3399/bjgpo.2022.0037
|View full text |Cite
|
Sign up to set email alerts
|

Comparing registered and resident populations in Primary Care Networks in England: an observational study

Abstract: BackgroundPrimary Care Networks (PCNs) were established in England in 2019 and will play a key role in providing care at a neighbourhood level within Integrated Care Systems (ICSs).AimTo identify PCN ‘catchment’ areas and compare the overlap between registered and resident populations of PCNs.Design & settingObservational study using publicly available data on the number of people within each Lower Layer Super Output Area (LSOA) registered to each General Practice (GP) in England in April 2021.MethodLSOAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Clinicians have reported that although many consultations can be safely managed by telephone, the remainder require in-person assessment, and both staff and patients have reported concerns about technological availability and skill (Greenhalgh et al, 2022). When used well, video consulting can overcome some of the drawbacks noted for telephone consulting, particularly around non-verbal communication and creating rapport (Donaghy et al, 2019;Payne and Clarke, 2023). For clinicians, these visual aspects may increase the quality and safety of consultations by allowing, for example, better checking of patient understanding, visual assessment of patients and better identification of safeguarding concerns (Atherton and Ziebland, 2016;Payne and Clarke, 2023).…”
Section: Video Consultingmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians have reported that although many consultations can be safely managed by telephone, the remainder require in-person assessment, and both staff and patients have reported concerns about technological availability and skill (Greenhalgh et al, 2022). When used well, video consulting can overcome some of the drawbacks noted for telephone consulting, particularly around non-verbal communication and creating rapport (Donaghy et al, 2019;Payne and Clarke, 2023). For clinicians, these visual aspects may increase the quality and safety of consultations by allowing, for example, better checking of patient understanding, visual assessment of patients and better identification of safeguarding concerns (Atherton and Ziebland, 2016;Payne and Clarke, 2023).…”
Section: Video Consultingmentioning
confidence: 99%
“…When used well, video consulting can overcome some of the drawbacks noted for telephone consulting, particularly around non-verbal communication and creating rapport (Donaghy et al, 2019;Payne and Clarke, 2023). For clinicians, these visual aspects may increase the quality and safety of consultations by allowing, for example, better checking of patient understanding, visual assessment of patients and better identification of safeguarding concerns (Atherton and Ziebland, 2016;Payne and Clarke, 2023).…”
Section: Video Consultingmentioning
confidence: 99%